RANCANG BANGUN WEBSITE INFORMASI BERBASIS WORDPRESS: STUDI KASUS SMAS ISLAM TERPADU DAAR ULUM - Sinuraya, Khairul Abdi; Agus, Raja Tama Andri; Nurhasanah, Nurhasanah; Iskandar, Iskandar (Smart Education, 2025)
Abstract: The advancement of information technology has encouraged schools to transition to digital media as a primary means of delivering clear and organized information. SMAS Islam Terpadu Daar Ulum recognized the need for a centralized, accessible, and professional information platform to improve communication between the school, students, parents, and the broader community. Previously, the dissemination of information was less effective, relying solely on social media and direct communication, which often lacked structure. To address this challenge, a school website was developed using the WordPress platform. The website was built in stages following the waterfall approach, covering phases from needs analysis to final evaluation. It features a responsive and attractive design compatible with various devices, and includes key sections such as school profiles, the latest news, and activity documentation. Testing showed that all features functioned according to the planned design. With the launch of this website, the school aims to enhance the effectiveness of information delivery while also strengthening its image in the digital era. Keyword: school website; wordpress; waterfall method; Abstrak: Perkembangan teknologi informasi kini mendorong sekolah-sekolah untuk mulai beralih ke media digital sebagai cara utama dalam menyampaikan informasi secara jelas dan teratur. SMAS Islam Terpadu Daar Ulum melihat perlunya sebuah wadah informasi yang terpusat, mudah diakses, dan terlihat profesional agar komunikasi antara sekolah, siswa, orangtua, dan masyarakat bisa berjalan lebih baik. Selama ini, penyampaian informasi masih belum maksimal karena hanya mengandalkan media sosial dan penyampaian langsung yang seringkali tidak terstruktur. Guna menjawab tantangan tersebut, dikembangkanlah sebuah website sekolah berbasis wordpress. Website ini dikembangkan secara bertahap melalui pendekatan waterfall, yang mencakup tahapan analisis kebutuhan hingga evaluasi akhir. Website yang dibuat memiliki tampilan yang menarik dan bisa menyesuaikan dengan berbagai perangkat, serta dilengkapi fitur-fitur seperti informasi profil sekolah, berita terbaru, dan dokumentasi kegiatan. Pengujian yang dilakukan membuktikan bahwa semua fitur berfungsi sesuai dengan desain yang telah dirancang. Dengan hadirnya website ini, diharapkan proses penyampaian informasi menjadi lebih efektif dan sekaligus membangun citra sekolah di era digital. Kata kunci: website sekolah; wordpress; metode waterfall;